PENGARUH PERSEPSI PENGEMBANGAN KARIER DAN FEAR OF SUCCESS TERHADAP KESEJAHTERAAN PSIKOLOGIS POLISI WANITA DI MAPOLDA DIY - admin; Estikomah . (Wahana Islamika: Jurnal Studi Keislaman, 2018)
As a law enforcement agency in Indonesia, the police must show good performance. In order to maintain and improve the performance of the police, the support of all personnel is indispensable, with the exception of the Policewomen. Policewomen performance will be good if they have good psychological well-being, so researching variables that can affect psychological well-being is very important. Based on this, this study aims to examine the effect of fear of success career development on the psychological well-being of Policewomen in Mapolda DIY This study uses a quantitative approach with the number of research subjects amounting to 137 consisting of Policewomen in Mapolda DIY. The analysis method used in this study is multiple linear regression analysis. The results of the study found that the perception of career development and fear of success had a positive and significant influence on psychological well-being. In addition, this study also found that the perception of career development has a greater influence on psychological well-being compared to the influence given by fear of success on psychological well-being.